Member of the Organizing Committee - Antoniou, Klitsa (My University, 2026)
This Silence has a Sound ... it is the Sound of a Horizon, The Collection Gallery Conference Space, Nicosia, Cyprus. Keynote Speakers: Krista Mikkola, Hesperia Iliadou, Gabriel Koureas.Sponsored by Cyprus Ministry of Culture and Education